Applying Precautionary Principle in Fisheries Management - Emmy Latifah; Moch Najib Imanullah (Jambe Law Journal, 2018)
The aim of this paper is to examine an applying the precautionary principle in fisheries management. Precautionary principle is a principle where the possibility exist of serious or irreversible harm, lack of scientific certainty should not preclude cautions action by decision-makers to prevent or mitigate such harm. This principle has been accepting in widely international environmental law so that with applying this principle in fisheries management, it could be expected to provide an opportunity to progress towards sustainable fisheries development.